Activated carbons derived from coconut shells as high energy density cathode material for Li-ion capacitors - Jain, Akshay (2014)
In this manuscript, a dramatic increase in the energy density of ~ 69 Wh kg−1 and an extraordinary cycleability ~ 2000 cycles of the Li-ion hybrid electrochemical capacitors (Li-HEC) is achieved by employing tailored activated carbon (AC) of ~ 60% mesoporosity derived from coconut shells (CS). The AC is obtained by both physical and chemical hydrothermal carbonization activation process, and compared to the commercial AC powders (CAC) in terms of the supercapacitance performance in single electrode configuration vs. Li. The Li-HEC is fabricated with commercially available Li4Ti5O12 anode and the coconut shell derived AC as cathode in non-aqueous medium. The present research provides a new routine for the development of high energy density Li-HEC that employs a mesoporous carbonaceous electrode derived from bio-mass precursors.